Safe and Successful Yttrium-90 Resin Microsphere Radioembolization in a Heavily Pretreated Patient with Chemorefractory Colorectal Liver Metastases after Biliary Stent Placement above the Papilla - Vlasios S. Sotirchos; Elena N. Petre; Karen T. Brown; Lynn A. Brody; Michael I. D’Angelica; Ronald P. DeMatteo; Nancy E. Kemeny; Constantinos T. Sofocleous (Case Reports in Hepatology)
We report a case of safe and successful yttrium-90 resin microsphere radioembolization in a patient with a long history of multiple recurrent colon cancer hepatic metastases progressing after hepatic resections, hepatic arterial chemotherapy, and multiple regimens of systemic chemotherapy. One month prior to radioembolization, a biliary stent was placed above the level of the ampulla to relieve tumor-related biliary obstruction and normalize bilirubin levels.